ROLE OF COLOR IN ILLUSTRATED JAIN MANUSCRIPTS (WITH REFERENCE TO ADIPURAN): सचित्र जैन पाण्डुलिपियों में रंग की भूमिका (आदिपुराण के सन्दर्भ में) - Jain, Srishti (International Journal of Research -GRANTHAALAYAH, 2014)
Color is of great importance in our India, without color, there is no basis for any object, person, color really tells us the nature of each other. The color or color refers to the color of the substance, red, yellow, blue. Depending on the combination of these, several distinctions of varna can be made. India is a religious country with different beliefs. Manuscripts have a special relationship with religion. Manuscripts are the best means of salvation for our teachers. One of them is the illustrated Jain manuscript Adipuran. The manuscript, which has been composed by Acharya Pushpadanta, depicts the life history of Lord Rishabhdev (the first Tirthankara) through paintings. The presented manuscript is stored in the scripture store of Terapanthiyan, the Digambar Jain big temple of Jaipur. Its clerical 1597 (AD 1540) is Falgun Shukla 13. Its writing work was done by a Brahmin man named Vishnudas and the paintings are made by Harinath Kayastha and his family. This 687-page manuscript has 541 colored illustrations corresponding to the biography of Tirthankara Rishabhdev. Mainly in the picture, the mineral color (made from a mixture of vegetable juices, ie the color made from the bark of clay stone trees, etc.) is the most used. Mainly ocher (red) Hironji (green) Ramaraj (yellow) ink (black) color is mainly used. The four colors used in the manuscript are symbols of Jainism, such as the red color (ocher) represents our inner vision, that is, the Siddha Parmeshti used in Jainism. Those who have attained salvation. Yellow color activates our mind. Green color gives peace. It helps in self-realization. Blue color is absorbent and does not allow the outside effect to go inside. Black color was used for writing in manuscripts. The ink for writing work was made with three methods. हमारे भारतवर्ष में रंग का बहुत महत्व है रंग के बिना किसी भी वस्तु, व्यक्ति का कोई आधार नहीं है सही मायने में रंग ही हमको एक दूसरे के स्वरूप को बताते हैं। वर्ण या रंग का अर्थ पदार्थ की रंगत से है लाल, पीला, नीला। इनके मिश्रण के आधार पर वर्ण के अनेक भेद किये जा सकते हैं। भारतदेश एक धर्म प्रधान देश है जिसमें विभिन्न मान्यतायें हैं। धर्म के साथ पाण्डुलिपियों का विशेष सम्बन्ध है पाण्डुलिपियाँ हमारे गुरूओं की मोक्ष साधना का उत्तम साधन है उनमें से एक है सचित्र जैन पाण्डुलिपि आदिपुराण। जिसकी रचना आचार्य पुष्पदंत ने की है पाण्डुलिपि में भगवान ऋषभदेव (प्रथम तीर्थंकर) के जीवन चरित को चित्रों के माध्यम से दर्शाया गया है। प्रस्तुत पाण्डुलिपि जयपुर के दिगम्बर जैन बड़ा मन्दिर तेरापंथियान के शास्त्र भण्डार में संग्रहित है। इसका लिपिकाल 1597 (ई. सन् 1540) फाल्गुन शुक्ल 13 है। इसका लेखन कार्य विश्नुदास नाम के ब्राह्मण व्यक्ति के द्वारा किया गया और चित्र हरिनाथ कायस्थ और उनके परिवार द्वारा बनाये गये हैं। 687 पृष्ठों की इस पाण्डुलिपि में तीर्थंकर ऋषभदेव के जीवनचरित के अनुरूप 541 रंगीन चित्र हैं। मुख्य रूप से चित्र में खनिज रंग (वनस्पति रसों के मिश्रण से निर्मित अर्थात् मिट्टी पत्थर वृक्षों की छाल आदि से बने रंग) का प्रयोग सर्वाधिक किया गया है। मुख्यतः गेरू (लाल) हिरोंजी (हरा) रामरज (पीला) स्याही (काला) रंग प्रमुख रूप से प्रयोग हुआ है। पाण्डुलिपि में प्रयुक्त चारों रंग जैन धर्म के प्रतीक हैं जैसे कि लाल रंग (गेरू) हमारी आंतरिक दृष्टि यानि कि जैन धर्म में प्रयुक्त सिद्ध परमेष्टी को दर्शाता है। जिन्होंने मोक्ष को प्राप्त कर लिया है। पीला रंग हमारे मन को सक्रिय करता है। हरा रंग शांति देता है। आत्मसाक्षात्कार में सहायक होता है। नीला रंग अवशोषक होता है वह बाहर के प्रभाव को अंदर नहीं जाने देता। काला रंग पाण्डुलिपियों में लेखनकार्य के लिये प्रयोग में लाया जाता था। लेखन कार्य के लिये स्याही तीन विधियों से बनायी जाती थी।